PENGARUH MODAL DAN TENAGA KERJA TERHADAP PRODUKSI INDUSTRI KECIL MEUBEL UTAMA DI KABUPATEN SUMBAWA - Arisa Dekayasa; Subhan Purwadinata (Fakultas Ekonomi dan Manajemen, 2022)
This study aims to determine the effect of capital and labor on the production of the main furniture small industry in the village of Often, Unter Iwes District, Sumbawa Regency. This research uses quantitative research methods. The population in this study were the owners and employees of Main Furniture, amounting to 17 people. The entire population is used as a sample or using a saturated sampling technique. Data was collected through a questionnaire. The data analysis techniques used are multiple linear regression, t and F tests, and the determinant coefficient test (R2). The results showed that capital and labor had a positive and significant effect on the total production of the Main Furniture Industry in Sumbawa Regency, either partially or simultaneously. The degree of influence of capital and labor on the total production of the Main Furniture Industry in Sumbawa Regency is 74.9%, while the remaining 25.1% is influenced by factors other than capital and labor variables.